New data on Apteroloma (Coleoptera: Agyrtidae) of central Asia and the Himalayas with a new synonymy - Růžička, Jan; Latella, Leonardo; Schawaller, Wolfgang (Zootaxa, 2014)
The distribution of Apteroloma anglorossicum (Semenov, 1890), A. harmandi (Portevin, 1903) and A. sillemi Jeannel, 1935 in central Asia and along the Himalayas is summarized, and the collecting circumstances and ecology of all three species from Gilgit District, Pakistan are described in detail. Revised diagnoses of all three species are provided, habitus and important morphological structures are illustrated, and available types have been examined. Apteroloma jankovskii Semenov and Znojko in Semenov, 1932 is confirmed as junior subjective synonym of A. anglorossicum. Apteroloma heinzi Schawaller, 1991 is newly treated as a junior subjective synonym of A. harmandi.